Chapter "Intensive" verbal prefixes in Archaic Latin - BERTOCCI, DAVIDE (Biblioteca di Studi Slavistici, 2017)
The goal of this paper is to give a brief outline of the synchronic conditions which trigger the emergence of aspectual values in Latin verbal prefixes. In particular, I will show that such a possibility is not the result of bare semantic effects, lexicalization of idioms or compounding strategies; rather, aspectual preverbation crucially has to do with syntactic factors, namely the argument structure of the verb, the prepositional character of the prefixes, and the interactions between those components.